AKUMULASI KADMIUM PADA DAGING IKAN BANDENG ACCUMULATION CADMIUM OF BANDENG FISH FLESH - Prabowo, Rossi (MEDIAGRO, 2005)
Analysis Biota irrigate is very  importance, because Cd heavy metal characteristic which bioakumulation and biomagnification. Bandeng one of materials consume human being which indirectly with process enchain food and will remove Cd heavy metal accumulation  to higher level organism like human being. This Research is executed  by using complete random research device. As for its formation consist of 4 group by 3 treatment group that is concentration 80 ppm, 135 ppm, and 180 ppm and also 1 group as control where each by 3 restating times. Cd  accumulate  analysis conducted in Chemical Laboratory UNNES with AAS technicsly. Research  result indicate that biggest accumulation at 180 ppm CdSO4  concentration at third week, this matter because ever greater Cd heavy metal concentration in water test than Cd accumulation  in  bandeng also will be ever greater, and  also longer disclosure time hence Cd accumulation will be progressively growing larger. From research be able biggest Cd accumulation in  treatment with concentration 180 ppm at third week equal to 22.32 ppm, the value have exceeded sill maximum limit determined by FDR New Zealand and also FAO that is mentioning sill Cd maximum limit in  fish equal to 1 ppm. Cd accumulate factor of bandeng between 0,173 - 16,525. Can be concluded that Cd accumulation in bandeng bared at CdSO4 various concentration will be advance degree in a row  improvement CdSO4 concentration  in water test, and disclosure time depth. Cd Concentration factor  in  bandeng mount its rate along the duration disclosure time with CdSO4. Cd Factor Concentration in bandeng the included in low category and range from 0,173 - 16,525. Keywords  :  Accumulate, Cadmium.